Leveraging Cloud Computing for Network Infrastructure Disaster Mitigation and Recovery (A Case Study at STIKI Malang) - Wahyu Andika Pratama; Koko Wahyu Prasetyo (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2025)
Disasters are unpredictable and destructive events that can severely impact information technology services. This study develops a disaster recovery plan focusing on leveraging cloud computing to enhance disaster mitigation and recovery for network infrastructure. Specifically, it examines critical information system services and network infrastructure at STIKI Malang. Utilizing Google Cloud Platform, the study proposes a novel network topology and disaster recovery procedures, excluding budgetary and insurance considerations. The research outputs include a cloud-based network topology model and a comprehensive disaster recovery procedure. These are designed to minimize service disruptions and incorporate an alert system for responding disturbances on information system applications. Additionally, the study provides a risk analysis and preventive measures, offering operational guidelines to mitigate disaster impacts effectively. The findings aim to enhance resilience and ensure continuity of critical services, providing a valuable framework for institutions facing similar challenges. This research underscores the transformative potential of cloud computing in disaster management, offering strategic insights into integrating cloud solutions for robust network infrastructure resilience.